First steps in retail management - Wrice, Mark. (South Yarra, Vic. : Macmillan Education Australia, 1998)
This book is about: The step uo to management; Service; Selling; Merchandising; Inventory; Loss prevention; Staff training; Employee relations; Finance; ...
Keywords: Marketing; Management; Retail trade -- Australia -- Management; Marketing -- Australia -- Management